Pneumatic concrete laminar structures revisited. A singular architectural structural type - Elena López-Ortiz; Paloma Pineda (VLC Arquitectura)
The 20th century was a time for architectural change, technical innovation and the search for affordable construction and prefabrication. In this context, pneumatic concrete laminar structures represent the advances towards a new architecture that could give answers to the challenges of the century. This work identifies the systems that were explored during that period and describes the experimental designs developed by W. Neff, H. Heifetz, H. Isler, D. B. South and D. Bini. In addition, the adaptation capability of this singular type and the reasons that caused the abandonment of these structure are also analysed.